Conceitos e transposição didática de genótipo e fenótipo: uma análise de livros didáticos - Silva, Aline Alves da (2017)
The history and philosophy of science can be used as subsidies to improve science teaching, including biology. For this improvement to occur, it is necessary to carry out researches to raise the historical aspects of concepts elaboration related to the scientific content present in schools and also the materials to support teachers, like textbooks. For that purpose, a study, from the 1950s to the present day on the conceptual development of genotype and phenotype, was carried out to provide theoretical subsidies for the analysis of these terms in high school biology textbooks. This research is justified by the need to evaluate how the concepts are presented in textbooks, since there is a need to adapt and revise the concepts according to the academic research notes, and also how the mere "knowledge used" is transposed to the "knowledge taught". The general objective of this study was to analyze how the concepts of genotype and phenotype are introduced in textbooks for basic education system. To find out the following questions were asked: Are the concepts of genotype and phenotype presented and transposed to textbooks respecting the scientific knowledge of each era? Is there historical recurrence in these materials of how the definition of these concepts came to be? The methodology is qualitative in nature, comprising data content analysis, which consists of three steps: pre-analysis, coding and categorization. The process of analyzing didactic transposition was carried out according to the following elements: Transformation Outsourcing, Internal Transformation, knowledge programmability, context-bound, biological aging and aging moral distance, textualization of knowledge, didactic creations and the old/new dialectic. Analyzing the results it was evidenced that the concepts of genotype and phenotype present in the respective textbooks did not follow the understanding of the scientific community of each era. Generally, the delay of the didactic transposition occurs, with respect to the development of the scientific knowledge. It is understood that part of this delay is acceptable, since it is very difficult for textbooks to be edited at the time of scientific research. However, authors and editors need to be concerned with the updates that emerge from scientific production, and care must be taken to ensure that there is no distancing of decades between the concepts presented in the teaching materials in relation to the compressions accepted by the scientific community. Regarding to analysis of the elements of the didactic transposition, it was noticed that the books usually present the contents of genotype and phenotype in a synthetic way, which may make it impossible to develop the scientific literacy of the students, leading them to see the genetics in a deterministic way, without considering the internal and external interferences for the constitution of the phenotype.